2009
DOI: 10.4162/nrp.2009.3.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of aloin, aloe-emodin, and aloesin; A comparative study using two in vitro absorption models

Abstract: Aloe products are one of the top selling health-functional foods in Korea, however the adequate level of intake to achieve desirable effects are not well understood. The objective of this study was to determine the intestinal uptake and metabolism of physiologically active aloe components using in vitro intestinal absorption model. The Caco-2 cell monolayer and the everted gut sac were incubated with 5-50 µM of aloin, aloe-emodin, and aloesin. The basolateral appearance of test compounds and their glucuronosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…The absorption percentages of aloin and aloesin were 7.53% and 21.33% (Park et al 2009b), and therefore supplementation levels of 0.005% to 0.5% aloin and aloesin diets accomplish plasma concentration of aloin and aloesin between 1.9-191 μM and 12.7-1270 μM, which cover in vitro efficacy levels (Park et al 2009b). Since aloin is known to exert diarrhea, we also conducted an in vivo study to determine the safe intake level and found that aloin at a concentration range of 0.005% to 0.1% of the diet did not cause diarrhea.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The absorption percentages of aloin and aloesin were 7.53% and 21.33% (Park et al 2009b), and therefore supplementation levels of 0.005% to 0.5% aloin and aloesin diets accomplish plasma concentration of aloin and aloesin between 1.9-191 μM and 12.7-1270 μM, which cover in vitro efficacy levels (Park et al 2009b). Since aloin is known to exert diarrhea, we also conducted an in vivo study to determine the safe intake level and found that aloin at a concentration range of 0.005% to 0.1% of the diet did not cause diarrhea.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Hu et al (2006) reported that the MAP kinase pathways may play an important role in early signaling events leading to the regulation of gene expression of phase II enzymes, including UGTs. We have previously demonstrated that aloesin is transformed to aloesin glucuronides/sulfates during intestinal absorption by UGT enzymes (Park et al 2009b), indicating that aloesin-regulated MAP kinase activity may also be involved in the absorption of aloesin. Moreover, in the present study, aloesin remarkably inhibited LTB 4 release, which possibly reduces the excessive accumulation of inflammatory mediators and cytokines on an inflamed colon.…”
Section: Discussionmentioning
confidence: 98%
“…After the muscularis was removed, the intestine tissue sample was placed in warm (37°C) Tyrode’s solution. [21] A section of 2–3 cm of the jejunum was isolated and cultured with fresh oxygenated Tyrode’s solution containing CN-DOX-IO at 37 °C. DOX-IO and free DOX were also tested as controls.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that aloe‐emodin was excreted by first‐order kinetics and the concentration–time curve of aloe‐emodin was shown to fit two‐compartment model after intragastric administration of aloe‐emodin (20 and 50 mg/kg) to rats (Feng et al, ). In Caco‐2 cell model and the everted gut sac model, the absorption rate of aloe‐emodin was ranged from 6.60% to 11.32%, and aloe‐emodin was mainly absorbed as a glucuronidated or sulfated form, suggesting that a significant amount was transformed during absorption (Park, Kwon, & Sung, ).…”
Section: Pharmacokineticmentioning
confidence: 99%